Code-Switching Between Romanized Bangla and English: A Sociolinguistic Study of Social Media Posts - M M Fahim Shahriar (Universitas Teuku Umar, 2026)
The Bangla language has a core national identity due to the fierce resistance of the 1952 language movement. Over time, a hybrid linguistic space has been created on social media for various factors. This sociolinguistic study explores the implementation of code-switching between Bangla text written in the Latin script known as Romanized Bangla and English in Bangladeshi social media, examining social and technical factors and structural patterns in online interactions. A descriptive quantitative analysis of social media posts and literature on code-switching, romanization, and digital communication in the Bangladeshi context was conducted to identify overarching themes. The primary data collected from social media postings were obtained from dominant platforms such as Facebook, Instagram, and WhatsApp, as per interaction between multilingual speakers. Our findings demonstrate that the intermixing of Bangla and English in a sentence or a clause is a widely prevailing pattern (e.g.,